Ecological-and-economic Approach to the use of Recycled Biomaterials as an Energy Resource - Myasnikova, Olga Y.; Lysytska, Svitlana M.; Migaleva, Tatyana E.; Bondarchuk, Nataliya V.; Vetrova, Ekaterina A. (International Journal of Energy Economics and Policy, 2019)
The problem of the traditional energy resources exhaustion which is also arising in the process of their exploitation as a factor of the environmental degradation is observed in the paper. The authors have analyzed the possibility of using alternative raw materials based on recycled plant biomaterials as renewable substitutes for energy sources. According to analytical data, it is shown that the biofuel demand as an alternative form of energy meets regulatory requirements that impose restrictions on the sulfur emission rate to the environment which are built up in the result of traditional combustible materials burning. The authors esteem the feasibility of all-around usage of various types of recycled biomaterials as a fuel. Within this framework, conducted study is a priority and promising direction for the world’s economy and energy, and the analysis of the main technical and economic characteristics of various types of waste biomass Keywords: Environmental safety, renewable energy sources, recycled biomaterials JEL Classifications: Q20, Q42, F52 DOI: https://doi.org/10.32479/ijeep.8511